Latent profiles of psychological resilience in patients with chronic disease and their association with social support and activities of daily living - Yingying Shi; Zhiqi Liang; Yunjie Zhang; Yiwen Zhou; Shishi Dong; Jufang Li; Gexin Gao (BMC Psychology)
Abstract Background This study aimed to identify different profiles of psychological resilience among patients with chronic disease and to further explore their association with demographic factors, social support, and activities of daily living (ADL). Methods A cross-sectional study was conducted between October and December 2023. A total of 460 patients with chronic disease were investigated by the demographic questionnaire, the Connor-Davidson Resilience Scale-10 item, the Social Support Rating Scale, and the Modified Barthel Index. Latent profile analysis was used to analyze the latent profiles of psychological resilience. The chi-square test, analysis of variance, and multinomial logistic regression were used to explore the factors associated with different profiles of psychological resilience. Results Psychological resilience in patients with chronic disease was classified into three profiles: vulnerable coping group, positive regulation group, and positive adaptation group. These three profiles showed unique relationships with the number of children, exercise status in recent years, subjective health status, objective support, subjective support, utilization of support, and ADL. Conclusions Most patients with chronic disease were classified into the positive regulation group. Healthcare workers need to pay more attention to patients with fewer children, less exercise, and lower subjective health, while it is especially important to improve patients’ objective support, subjective support, utilization of support, and ADL.